Identification of stably expressed quantitative trait loci for grain yield and protein content using recombinant inbred line and reciprocal introgression line populations in rice - Cheng, Lirui; Xu, Qin; Zheng, Tianqing; Ye, Guoyou; Luo, Chenggang; Xu, Jianlong; Li, Zhikang (Wiley, 2013)
Improvements of rice (Oryza sativa L.) grain yield and protein content are important breeding objectives. Two hundred forty recombinant inbred lines (RILs) derived from a cross between japonica cultivar Xiushui09 and indica breeding line IR2061‐520‐6‐9 were used to identify quantitative trait loci (QTLs) affecting grain yield per plant (GYP) and protein content (PC) in rice. A total of five main‐effect QTLs (M‐QTLs) were identified on chromosomes 2, 4, 7, 10, and 12, which collectively explained 50.06% of the total phenotypic variance. As for PC, a total of four M‐QTLs were identified on chromosomes 2, 5, 10, and 11, which explained 41.44% of the total phenotypic variance. A total six pairs of epistatic QTLs (E‐QTLs) were identified. Furthermore, the M‐QTLs for GYP and PC detected in the RIL population were confirmed by two sets of BC2F6 reciprocal introgression lines (ILs) derived from the same parents and tested in Sanya and Hangzhou. The results indicated that four M‐QTLs (qGYP‐7 and qGYP‐12 for GYP and qPC‐10 and qPC‐11 for PC) showed stable expressions and consistent pyramiding effects across different environments under different genetic backgrounds. The ILs with pyramided nonallelic alleles at M‐QTLs for GYP from Xiushui09 in IR2061‐520‐6‐9 genetic background or the alleles of M‐QTLs for PC from IR2061‐520‐6‐9 in Xiushui09 genetic background provided some useful information on marker‐assisted selection (MAS) for developing either higher GYP or higher PC cultivars. Two lines, XS‐198 and IR146, with favorable alleles at four M‐QTLs from the two parents showed high GYP and PC and thus could be directly used in production.